IT-Based Education with Online Labs in the MENA Region: Profling the Research Community - Salah, Razwan Mohmed (2015)
Education plays a primary role in developing countries, fostering their economy and augmenting their human potential. It is now easier to learn newest methods and techniques in many fields, particularly in engineer- ing and science, where IT-based educational tools - such as online laboratories - have been instrumental to improve the teaching and learning process. Online laboratories are widely used in several universities around the world, particularly in developed countries. There is evidence that online laboratories have a positive effect on the students’ skills and promote cooperative and collaborative learning by allowing them to work remotely without restrictions. This led to a quality increase of the teaching and learning process. Likewise, students from other countries, namely in the Middle East and North Africa (MENA) region, could also benefit from using online labs. This paper studies the existing collaboration among the researchers working with online labs, in the MENA region, by reviewing a selection of articles from conferences and journals. The patterns of cooperation and collaboration among them are discussed and analyzed, as well. In the authors’ opinions, the community characterized in this paper should establish more collaboration links in order to strength its capacity of influencing the adoption of online labs, in that region.